JBotEvolver: A versatile simulation platform for evolutionary robotics - Duarte, M. (2022)
This paper introduces JBotEvolver, a versatile simulation platform for research and education in evolutionary robotics (ER). JBotEvolver is a Java-based open-source, cross-platform framework available at https://code. google.com/p/jbotevolver/ under the GNU GPL. JBotEvolver has been used in a number of previous ER studies of our research group, from offline evolution to online evolution and learning, and from single to multirobot systems (for examples see Duarte et al. (2014a,b); Silva et al. (2012a,b)), and in a number of undergraduate and graduate courses at ISCTE-IUL